TRANSFORMASI TRANSAKSI PENJUALAN KERAJINAN TANGAN DI SUKU BADUY DESA KANEKES MELALUI PENGGUNAAN METODE QRIS - Eli Apud Saepudin; Asnawi Asnawi; M. Nassir Agustiawan (Indonesian Collaboration Journal of Community Services, 2023)
Woven clothes, key chain crafts, traditional Baduy clothes, romal, bebed, shawls, sides, sarongs, bags, nyiruan honey, odeng honey, palm sugar, powdered palm sugar, scarves, bamboo teapots and glasses, machetes, t-shirts and much more again original Baduy handicrafts. Baduy handicrafts are creative works of local wisdom of the Baduy people and boost the economy of the Baduy tribe, usually made by women who have known weaving from the time of their ancestors. Generally, when they are teenagers, mothers in Baduy teach their children to learn to weave, to produce 1 piece of woven cloth that takes 2 months. Many tourists who visit Baduy complain when they buy Baduy souvenirs but don't bring a lot of money because they still don't accept digital payments and end up failing to buy Baduy souvenirs. On Sunday, June 11, PKM FISIP Bina Bangsa University, which was attended by 50 Communication Science students and accompanied by 5 Lecturers with the aim of providing socialization and service to the Baduy community about the importance of digital payments in the modernization era